Evaluation of the Synergistic Antioxidant Effect of Resveratrol and Zataria multiflora Boiss Essential Oil in Sodium Alginate Bioactive Films - Hashemi, Mahsa; Hashemi, Mohammad; Amiri, Elham; Hassanzadazar, Hassan; Daneshamooz, Shahrzad; Aminzare, Majid (Current Pharmaceutical Biotechnology, 2019)
Background: Biodegradable films are appropriate alternatives to synthetic polymers due to their potential to enhance food safety and their function as a carrier for wide a range of food additives especially natural antioxidants. Objective: The aim of this study was to compare the potential antioxidant activities of sodium alginate films containing resveratrol (RES) alone and in combination with Zataria multiflora essential oil (ZEO) using an in vitro model. Methods: At first, the major chemical compositions of ZEO were evaluated by GC/MS. Then, the amount of phenolic compounds of sodium alginate films were evaluated by total phenolic contents assay and antioxidant activities of films were evaluated by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Finally, the concentrations of ZEO and RES which showed better antioxidant activities in sodium alginate films were incorporated to films in combination forms to evaluate their synergistic effects. Results: According to gas chromatography-mass spectrometry (GC/MS) analysis, 35 compounds of ZEO were identified and Thymol (37.94%), p-Cymene (9.50%) and 3-Carene (4.98%) were the most important compounds of essential oil, respectively. The results of the radical scavenging evaluations, showed better antioxidant activities of the films containing RES than the films containing ZEO and Butylated hydroxytoluene (BHT). Also, the combined uses of ZEO and RES into alginate films had the synergistic effects (P<0.05). Conclusion: Therefore, it can be concluded that alginate films incorporated with the combination of ZEO and RES is the appropriate option to postpone the oxidative reactions and can be used as natural antioxidant in the food packaging industry.
Keywords: radical scavenging activity